PREVALENCE AND RISK FACTORS ASSOCIATED wITH ENTERIC INFECTION IN LAYER CHICKEN - M.Geetha; K.M.Palanivel; G.Selvaraju; G.A. Balasubramaniam; T.R. Gopalakrishnmurthy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Enteric diseases of layer chicken are one of the major causes associated with economic losses to layer poultry farmers. An epidemiological investigation was carried out to analyse the role of risk factors associated with economic important enteric diseases viz. colibacillosis, necrotic enteritis, coccidiosis and Newcastle disease. Risk factors associated with disease occurrence were assessed by relative risk (RR) and odds ratio (OR). There was a strong positive association between occurrence of colibacillosis with other diseases, viz necrotic enteritis with age of chicken and concurrent coccidiosis. Similarly there was a strong positive association between the occurrence of coccidiosis with age of chicken and system of management. The occurrence of Newcastle disease was causally associated with the strain of chicken.